Management of Central Serous Chorioretinopathy Using Focal Laser Photocoagulation: A Case Report - Rezandi Aziztama; Ramzi Amin; A.K. Ansyori (Sriwijaya Journal of Ophthalmology, 2023)
Introduction: Central serous chorioretinopathy (CSC) has the main symptoms of choroidal thickening, detachment of retinal pigment epithelium (RPE), and presence of subretinal fluid. Treatment of CSC is indicated for cases with SRF persisting for more than 4 months, decreased visual acuity, history of recurrence, or history of previous CSC in other eyes with poor visual outcome. This case report aims to describe the management of CSC using focal laser photocoagulation. Case presentation: A man, 41 years old, living in the city, came with complaints of sudden blurred vision in his left eye when he woke up 3 months ago. This complaint is accompanied by a decrease in the ability to see in the middle. There are no vision complaints such as flashes of light, no blurred vision such as tunnels or closed curtains, no red eyes, pain, or eye discharge. On ophthalmological examination, there was a decrease in visual acuity oculi sinistra (OS) 6/12, intraocular pressure within normal limits, and orthophoria. On examination of the posterior segment of the OS, a decreased positive foveal reflex was found. Fluorescent angiography fundus photo examination showed central serous chorioretinopathy OS. This patient was diagnosed with central serous chorioretinopathy oculi sinistra. Management is given to patients in the form of disease-related education, laser focal photocoagulation OS, clobazam 10 mg/24 hours, eye drops oxymetazoline HCl 1 drop in the left eye/8 hours. Conclusion: Treatment with laser focal photocoagulation is beneficial in the clinical improvement of cases of central serous chorioretinopathy.